2016
DOI: 10.4103/0970-9185.182104
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of epidural dexmedetomidine and clonidine with bupivacaine in patients undergoing lower limb orthopedic surgeries

Abstract: Background and Aims:Alpha (α-2) adrenergic agonists have both analgesic and sedative properties when used as an adjuvant in regional anesthesia. A prospective randomized double-blind study was carried out to evaluate the efficacy of epidural route and to compare the efficacy and clinical profile of dexmedetomidine and clonidine as an adjuvant to bupivacaine with special emphasis on their quality of analgesia, sedation and the ability to provide the smooth intra-operative and postoperative course.Material and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 35 publications
9
32
0
Order By: Relevance
“…Our study has shown that the addition of either 1.5μg/kg dexmedetomidine or 2μg/kg clonidine as adjuvant to epidural Ropivacaine improves the quality of anesthesia and efficacy of local anaesthetic agent, which was supported by the previous studies. 11,12,13 Onset and peak levels of analgesia provided by both drugs dexmeditomidine> Clonidine) were statistically significant in our study which was in concordance with the observations of Bajwa et al 11 Unlike our study Salgado et al 13 and Shaikh SI et al 14 found no statistical significance in the onset and peak levels of analgesia provided by both drugs. But it has to be noted that the dose used by them for the study was less than ours.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Our study has shown that the addition of either 1.5μg/kg dexmedetomidine or 2μg/kg clonidine as adjuvant to epidural Ropivacaine improves the quality of anesthesia and efficacy of local anaesthetic agent, which was supported by the previous studies. 11,12,13 Onset and peak levels of analgesia provided by both drugs dexmeditomidine> Clonidine) were statistically significant in our study which was in concordance with the observations of Bajwa et al 11 Unlike our study Salgado et al 13 and Shaikh SI et al 14 found no statistical significance in the onset and peak levels of analgesia provided by both drugs. But it has to be noted that the dose used by them for the study was less than ours.…”
Section: Resultssupporting
confidence: 82%
“…But it has to be noted that the dose used by them for the study was less than ours. Our study showed statistically significant sedation score in the Dexmeditomidine group (RD) compared to the other groups which was similar to findings of the Bajwa SJ et al 11 , Saravana Babu M et al 12 ,Shaikh SI et al 14 andSchnaider TB et al 15 ,…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Although clonidine dose (2 µg/kg) used was higher than dexmedetomidine (1 µg/kg) it resulted in lesser motor blockade and sedation scores. 11 However, the haemodynamic parameters compared between the two groups were similar and statistically insignificant. 11 A study was conducted using 1 µg/kg of dexmedetomidine or clonidine in addition to epidural ropivacaine (15 ml) and they observed to have statistically insignificant difference with respect to haemodynamic parameters and motor blockade.…”
Section: Discussionmentioning
confidence: 97%
“…[12] Shaikh et al opined that dexmedetomidine is a superior neuraxial adjuvant to bupivacaine when compared to clonidine for early onset of analgesia,stable cardio-respiratory parameters and prolonged postoperative analgesia. [13] Bajwa et al studied dexmedetomidine and clonidine, in epidural anaesthesia and concluded that dexmedetomidine is a better neuraxial adjuvant compared to clonidine for providing early onset of sensory analgesia, prolonged post operative analgesia and adequate sedation. [14] The above studies supports our finding that dexmedetomidine as adjuvant to local anesthetics provides both early onset of block and prolongs the duration of analgesia.Vaidya et al carried out a prospective double blind study to see whether the sympathomimetic effect of intrathecal ketamine attenuates bupivacaine induced hypotension and bradycardia.…”
Section: Discussionmentioning
confidence: 99%